INTEGRATION OF THE BALTIC STOCK MARKETS WITH GLOBAL MARKETS DURING THE PREVIOUS DECADE - Anmar Pretorius (Baltic Journal of Economic Studies)
The three Baltic countries of Estonia, Latvia and Lithuania achieved independence in 1991. In the period between 1993 and 1996, the three Baltic countries established their own stock exchanges. The dualistic nature of these economies – namely, relatively young democracies with newly established stock exchanges on the one hand and high levels of integration into Europe due to EU and Euro area membership on the other – gives rise to the question of whether these stock exchanges are integrated with the developed markets or the emerging markets. The objective of this study is to empirically ascertain the extent of stock market integration of the Baltic markets with global stock markets. The extent of integration with developed and emerging markets is established. The preliminary analysis compares the economic structures of the three domestic economies, the industry contributions of the stock exchanges, and the major international countries investing in the three stock markets. The subsequent stage of the analysis entails the utilisation of principal component analysis. The specified number of latent factors behind global systemic risk are extracted from the panel data set employing factor analysis. Subsequently, these factors serve as independent variables, thereby explaining the variation in returns observed in each country's stock market. The explanatory power of the regressions thus indicates the degree of integration of the stock market with global markets. Despite similar economic structures, with the same sectors contributing almost equally to total output, the sectors represented on their stock exchanges are different. Financials contribute the most to the Estonian stock exchange, followed by utilities. In Lithuania, utilities dominate, with telecommunications in second place. More than half of the Latvian market is made up of utilities and another quarter of financials. Investors from a variety of countries have made investments in the three Baltic exchanges, with the composition of these investments undergoing notable shifts over the past decade. A factor analysis indicates that these Baltic markets are more integrated with the global developed stock markets than with emerging markets. However, these levels of integration are low, and movements on these exchanges are potentially more reflective of country- or region-specific factors than of global factors. There are some indications that the Estonian stock exchange was less integrated in 2019 than in 2010, while the other two show signs of increasing integration.